The Influence of Patient Experience and Patient Engagement on Patient Loyalty Through Inpatient Satisfaction as an Intervening Variable at RSUD Latersia Binjai - Selly Gabel Aprilliani Depari; Beby Karina Fawzeea Sembiring; Evawany Yunita Aritonang (PT FORMOSA CENDEKIA GLOBAL, 2025)
Competition in the healthcare industry is increasing, requiring hospitals to provide better services to retain patients. Patient loyalty is a crucial factor in a hospital's sustainability and is influenced by various aspects, including patient experience and patient engagement. This study aims to analyze the influence of patient experience and patient engagement on patient loyalty, with inpatient satisfaction as an intervening variable at Latersia Hospital Binjai. A quantitative method with the Partial Least Square – Structural Equation Modeling (PLS-SEM) approach was used. The results indicate that patient experience and patient engagement have a positive and significant effect on patient satisfaction, which subsequently influences patient loyalty. The better the patient’s experience and engagement in their care, the higher their satisfaction, leading to increased loyalty to the hospital. Additionally, patient satisfaction serves as a mediating variable, strengthening the relationship between patient experience, patient engagement, and patient loyalty. This study contributes to the development of strategies for improving hospital services, focusing on enhancing patient experience and engagement to increase satisfaction and loyalty. Understanding the factors that influence patient loyalty enables hospitals to enhance their competitiveness and deliver higher-quality healthcare services to the community.